2013
DOI: 10.1088/0957-4484/24/19/195301
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of TiO2nano-to-microscale structures using UV nanoimprint lithography

Abstract: TiO2-nanoparticle-dispersed resin was prepared to form various nanoscaled structures using UV nanoimprint lithography (UV NIL). This resin-made of TiO2 nanoparticles, a monomer, solvent, and UV initiator-showed variations in refractive index depending on the nanoparticle concentration. TiO2 nano-to-microscale patterns were fabricated on various substrates such as Si wafer and glass, and even on flexible substrates, by using UV NIL, which offers advantages such as low cost, large area, and high throughput. Low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…In contrast to EBL, the mechanical properties of the resist layer are of prime importance as the Young’s modulus of the resist must be lower than the Young’s modulus of the mold. In hot embossing NIL, thermoplastic resists are imprinted with the mold at temperatures 70–90° above T g , then cooled before releasing from the mold ( Figure 2B ) ( Guo, 2007 ; Choi et al, 2013 ). Alternatively, low-viscosity UV-curable resists can be cured by UV light at ambient temperatures while being imprinted with the mold ( Schulz et al, 2000 ; Guo, 2007 ).…”
Section: Technologies To Create Nano-architecturementioning
confidence: 99%
“…In contrast to EBL, the mechanical properties of the resist layer are of prime importance as the Young’s modulus of the resist must be lower than the Young’s modulus of the mold. In hot embossing NIL, thermoplastic resists are imprinted with the mold at temperatures 70–90° above T g , then cooled before releasing from the mold ( Figure 2B ) ( Guo, 2007 ; Choi et al, 2013 ). Alternatively, low-viscosity UV-curable resists can be cured by UV light at ambient temperatures while being imprinted with the mold ( Schulz et al, 2000 ; Guo, 2007 ).…”
Section: Technologies To Create Nano-architecturementioning
confidence: 99%
“…Nanoparticle suspensions have also been used for direct nanoimprinting with a so PDMS mold. 50 This approach has been used to directly fabricate threedimensional structures of multicomponent oxides like indium tin oxide and nickel ferrite. 51,52 Photosensitive ethylhexanoatebased oxide patterning has been reported that utilizes photobreakable precursors rather than photo-curable monomers.…”
Section: Introductionmentioning
confidence: 99%
“…The replicated PDMS mold was removed from the imprinted substrate when the resin was cured by the UV light. Nano‐ to microscale structures composed of Fe 2 O 3 nanoparticles on various substrates can be fabricated through this UV imprint lithography …”
Section: Methodsmentioning
confidence: 99%